2018
DOI: 10.3389/fimmu.2018.01176
|View full text |Cite
|
Sign up to set email alerts
|

Centrin-Deleted Leishmania donovani Parasites Help CD4+ T Cells to Acquire Th1 Phenotype and Multi-Functionality Through Downregulation of CD200–CD200R Immune Inhibitory Axis

Abstract: The protozoan parasite Leishmania has evolved several strategies to undermine host defense mechanisms by inducing Th2-type adaptive immunity and suppressing effector functions of Th1 phenotype. In our earlier studies, using centrin gene-deleted Leishmania (LdCen−/−) parasites as an immunogen, we have shown induction of an effective Th1-type immunity and robust memory responses that mediate protection against virulent challenge. However, role of inhibitory signals in Leishmania vaccine induced immunity in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…We have previously observed critical differences in the immunological responses following inoculation with LmexCen −/− parasites compared to their wild type counterparts 12 . This was also observed in L. donovani, L. major , and L. mexicana centrin mutants 10,12,32,33 . In this study, we explored the metabolic drivers of the immunological differences between infection with the parental or mutant strains and demonstrated that immunization with LmexCen −/− parasites results in unique metabolic changes, compared to naïve and Lmex WT infected mice.…”
Section: Discussionsupporting
confidence: 59%
“…We have previously observed critical differences in the immunological responses following inoculation with LmexCen −/− parasites compared to their wild type counterparts 12 . This was also observed in L. donovani, L. major , and L. mexicana centrin mutants 10,12,32,33 . In this study, we explored the metabolic drivers of the immunological differences between infection with the parental or mutant strains and demonstrated that immunization with LmexCen −/− parasites results in unique metabolic changes, compared to naïve and Lmex WT infected mice.…”
Section: Discussionsupporting
confidence: 59%
“… 12 This was also observed in L. donovani , L. major , and L. mexicana centrin mutants. 10 , 12 , 42 , 43 Immunization with LmCen −/− and LmexCen −/− has been shown to confer protection against homologous and heterologous challenges. 10 , 11 , 12 , 13 , 44 However, the immune mechanisms of protection differed in these two immunization regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the protective response of vaccine candidates, which have been evaluated in both, experimental and human leishmaniasis, has also been linked with the production of pro-inflammatory cytokines in vaccinated individuals 17,20 . Further, the multifunctional antigen experienced CD4 + T cells is an important determinant of disease resistant as well 30,42,43 . The multifunctional nature of the CD4 + T cells not only helps the host to combat infection efficiently but also plays a significant role in the early conversion of effector T cells to their memory phenotypes 31,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings revealed that parasite upregulates the expression of immune inhibitory receptors viz., CD200, CD200R, and CD300a on the surface of macrophages and dendritic cells to dampen their effector properties for survival and proliferation 30,31,32 . Further, the abrogation of CD200R and CD300a signals in L. donovani infected animals was associated with the early elimination of parasites from their visceral organs that was found correlated with the increased functionality of antigen experienced CD4 + and CD8 + T cells 31,32 .…”
Section: Introductionmentioning
confidence: 99%